Conservation implications of low contemporary connectivity along the Mid‐Atlantic Ridge in hydrothermal vent gastropods - E. Portanier; A. Tran Lu Y; F. Pradillon; C. Daguin‐Thiébaut; S. Ruault; P. Collins; E. Omnes; S. Fuchs; J. Carlsson; D. Jollivet; M. Matabos (Conservation Biology, 2026)
Polymetallic sulfide deposits produced at hydrothermal vent fields are targets for mining exploitation along the Mid‐Atlantic Ridge, threatening the functioning and resilience of vent ecosystems that provide multiple ecosystem services. Knowledge about connectivity between vents will inform conservation practices. The present‐day genetic structure and demographic history of the two vent‐dwelling gastropod species, Lepetodrilus atlanticus and Peltospira smaragdina , were investigated using more than 15,000 single‐nucleotide polymorphisms and mt Cox1 sequences. Each species comprised three genetic groups. Genetic breaks were stronger for L. atlanticus , separating three distinct operational taxonomic units (5°S, Broken Spur at 29°N, and the Azorean vent fields near 37°N). Peltospira smaragdina was also geographically separated into three groups: Broken Spur, TAG, and Snake Pit (23–29°N); Lucky Strike (37°N); and Moytirra (45°N). A semipermeable zone was detected south of Rainbow (35°N), similar to that of vent mussels in this area, suggesting the presence of a multispecies hybrid zone. Demographic inferences supported secondary contact between most pairs of metapopulations for both species, but the time since contact was insufficient for allele frequencies to rehomogenize. Gene flow between vent fields may be sporadic and rare or restricted by genetic barriers. The fragmentation of species into isolated metapopulations may reduce their resilience to disturbance and create the need for specific conservation measures. Isolated populations (e.g., Moytirra for P. smaragdina , 5°S and Broken Spur for L. atlanticus ), source populations (e.g., Lucky Strike for P. smaragdina ), admixture areas, and sites that may act as stepping stones within a metapopulation must be protected from deep‐sea mining. An average distance of

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Experimental study on the interaction of falling films and sprays during cleaning - M. Joppa; R. Schade; T. Hanisch; C. Golla; E. Fuchs; M. Mauermann (Food and Bioproducts Processing, 2026)

Innovative cleaning system with movable cavitation nozzle based on the hunting behaviour of the pistol shrimp - R. Murcek; E. Fuchs; J.F. Mauer; M. Finster; M. Mauermann (Food and Bioproducts Processing, 2026)

Didesmethylrocaglamide cytotoxic activity in high grade serous ovarian cancer in preclinical in vitro and in vivo models - Elizabeth N. Kaweesa; Tyler A. Wilson; Jaqueline M. Bazioli; Li Pan; A. Douglas Kinghornb James R. Fuchs; Joanna E. Burdette (Phytochemistry Letters, 2025)

Didesmethylrocaglamide Cytotoxic Activity in High Grade Serous Ovarian Cancer in Preclinical In Vitro and In Vivo Models - Elizabeth N. Kaweesa; Tyler A. Wilson; Jaqueline M. Bazioli; Li Pan; A. Douglas Kinghorn; James R. Fuchs; Joanna E. Burdette (Phytochemistry Letters, 2025)

Decode-STS: Deciphering the landscape of canine soft-tissue sarcoma using spatially defined proteomics and transcriptomics - D. Fuchs; E. Markkanen; H. Ech-Cherif; S. Aghaabbasi; A. Pöschel; E. Beebe; L. Laura; W. Wolski; F. Guscetti; M. Nolff (Journal of Comparative Pathology, 2025)

Implementation of Cognitive (Neuropsychological) Interventions for Older Adults in Clinical or Community Settings: A Scoping Review - Kerryn E. Pike; Lily Li; Sharon L. Naismith; Alex Bahar-Fuchs; Alessandra Lee; Inga Mehrani; Adam Bentvelzen; Nicola T. Lautenschlager; Megan E. O’Connell; Irene Blackberry; Loren Mowszowski (Neuropsychology Review, 2025)
Despite compelling evidence that cognitive interventions for older adults improve cognition, mood, and everyday function, few are implemented in clinical or community practice. This scoping review aims to understand the implementation frameworks and methods used and their contribution to implementation success of cognitive interventions for older adults. We followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis extension for Scoping Reviews (PRISMA-ScR), and searched CINAHL, EMBASE, MEDLINE, and PSYCINFO databases, using terms related to cognitive interventions, implementation, and older adults. This resulted in 5002 studies, of which 29 were included following an iterative process. Most studies reported on implementation of cognitive stimulation for people with dementia. Only four studies used formal implementation frameworks, with three using RE-AIM, and one a process evaluation using complexity theory. The most frequently addressed implementation concepts were Acceptability, Feasibility, and Effectiveness, while Cost, Cost-Effectiveness, and Maintenance were rarely reported. Solutions to common barriers included the importance of good stakeholder relationships and engagement, a manualised intervention flexible enough to adapt to the context, and ensuring facilitators were well-trained, confident, and enthusiastic.

Grapevine red blotch virus detection in the vineyard: Leveraging machine learning with VIS/NIR hyperspectral images for asymptomatic and symptomatic vines - E. Laroche-Pinel; K. Singh; M. Flasco; M.L. Cooper; M. Fuchs; L. Brillante (Computers and Electronics in Agriculture, 2025)

Human endothelial colony forming cells (ECFCs) require endothelial protein C receptor (EPCR) for cell cycle progression and angiogenic activity - Sarah E. J. Chambers; Jasenka Guduric-Fuchs; Edoardo Pedrini; Pietro M. Bertelli; Chutima Charoensuk; Elisa Peixoto; Varun Pathak; Hamza I. Alhamdan; Ruoxiao Xie; Anna Krasnodembskaya; Judith Lechner; Alan W. Stitt; et al. (Angiogenesis, 2025)
Vascular repair and regeneration are critical for tissue homeostasis. Endothelial colony forming cells (ECFCs) are vessel-resident progenitors with vasoreparative capacity and they offer an important avenue for allogeneic cytotherapy to achieve perfusion of ischemic tissues. Endothelial Protein C Receptor (EPCR) has been proposed as a marker for vascular endothelial stem cells, but its precise role in ECFC biology remains unknown. The current study has investigated the biological relevance of EPCR in ECFC function. Our data show that over 95% of ECFCs exhibit high EPCR expression. These levels surpassing CD34 and CD157, positions EPCR as a new robust ECFC immunophenotypic marker, alongside established markers CD31 and CD105. Functionally, depleting EPCR expression in ECFCs significantly diminished angiogenic activity, including proliferation, migration and tube formation. This knockdown also altered normal ECFC barrier function. Transcriptomic analysis indicated that knockdown of EPCR led to enrichment of gene signatures for cell cycle, TGF beta, and focal adhesion kinases. G1 cell cycle arrest was confirmed in ECFCs with depleted EPCR. Mechanistically, EPCR knockdown led to increased release of TGFβ2 and SMAD2/3 activation, coupled with increased p21, decreased pFAK, and increased transgelin. Additionally, we showed that quiescent ECFCs showed significantly lower EPCR expression when compared to proliferating ECFCs. In agreement with this, cell sorting experiments demonstrated that ECFCs with the highest EPCR expression exhibited the highest clonogenic capacity. In summary, our findings highlight that EPCR expression in ECFCs is critical for their angiogenic activity, by modulating cell cycle progression. Graphical abstract

Quaternary intensification of spine epibiosis in the cidaroid echinoid Eucidaris: implications for anthropogenic impacts - Elizabeth Petsios; Corinne E. Fuchs; Michal Kowalewski; Paul Larson; Roger W. Portell; Carrie L. Tyler (Frontiers in Marine Science, 2025)
Echinoids are an integral part of present-day and ancient marine trophic webs, and they host a variety of mutualistic, commensalistic, and parasitic epibionts on their spines and test. Cidaroid echinoid (slate pencil urchins) spines in particular are commonly colonized by epizoans. Eucidaris in the western Atlantic and eastern Pacific today are notable for the frequency and intensity of calcifying, non-calcifying, and galling colonization on their spines. While moderate levels of spine colonization may provide camouflage and other benefits to the host, a high density of encrusters may instead reduce host fitness, and galling is invariably parasitic. Significant environmental changes in the equatorial and sub-equatorial western Atlantic and eastern Pacific necessitate a paleobiological approach to constrain the timing of changes in epibiosis intensity on Eucidaris . Here, we compare rates of spine colonization in present-day Eucidaris populations with ancestral Pliocene Eucidaris assemblages. We find that Pliocene spines show no evidence of parasitic galling, and significantly less evidence of epibiosis than their present-day descendants in both the Atlantic and Pacific. This holds true even after accounting for taphonomic processes that would preferentially erase evidence of non-calcifying colonization. We propose that the high intensity of colonization on present-day Eucidaris spines is a relatively recent development and may reflect human-induced habitat degradation in the region, underscoring the need for further investigation into this biotic interaction.

Effectiveness of ozone nanobubble treatments on high biomass cyanobacterial blooms: A mesocosm experiment and field trial - Justin D. Chaffin; David E. Berthold; Eugene C. Braig; Josh D. Fuchs; Rachel S. Gabor; Stephen J. Jacquemin; Haley E. Kuhn; Lillian D. Labus; H. Dail Laughinghouse; Forrest W. Lefler; Heath E. Mash; Heather A. Raymond; et al. (Journal of Environmental Management, 2024)

Association of Metal Cations with the Anti-PF4/Heparin Antibody Response in Heparin-Induced Thrombocytopenia - Jason B. Giles; Kiana L. Martinez; Heidi E. Steiner; Andrew Klein; Aikseng Ooi; Julie Pryor; Nancy Sweitzer; Deborah Fuchs; Jason H. Karnes (Cardiovascular Toxicology, 2024)

Long sediment-laden algal turf likely impairs coral recovery on Florida’s coral reefs - A. Duran; K. E. Speare; C. Fuchs; T. C. Adam; L. Palma; M. W. Miller; L. Collado-Vides; A. R. Harborne; D. E. Burkepile (Coral Reefs, 2024)

Impacts of irregularly-distributed acidified brine flow on geo-chemo-mechanical alteration in an artificial shale fracture under differential stress - Samantha J. Fuchs; Dustin Crandall; Johnathan E. Moore; Mayandi Sivaguru; Bruce W. Fouke; D. Nicolas Espinoza; Ange-Therese Akono; Charles J. Werth (International Journal of Greenhouse Gas Control, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

When colors mislead: Genomics and bioacoustics prompt re-classification of Asian flycatcher radiation (Aves: Niltavinae) - Kritika M. Garg; Chyi Yin Gwee; Balaji Chattopadhyay; Nathaniel S. Ng; Dewi M. Prawiradilaga; Gabriel David; Jérôme Fuchs; Hung Le Manh; Jonathan Martinez; Urban Olsson; Vuong Tan Tu; Sophea Chhin; et al. (Molecular Phylogenetics and Evolution, 2024)

A multi-criteria drought resistance assessment of temperate Acer, Carpinus, Fraxinus, Quercus, and Tilia species - C. Leuschner; S. Fuchs; P. Wedde; E. Rüther; B. Schuldt (Perspectives in Plant Ecology, Evolution and Systematics, 2024)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Standardisation and future of preclinical echocardiography - Caroline E. O’Riordan; Philippe Trochet; Magdelena Steiner; Dieter Fuchs (Mammalian Genome, 2023)

Genome‐wide SNPs confirm plumage polymorphism and hybridisation within a Cyornis flycatcher species complex - Elize Y. X. Ng; Siqi Li; Dezhi Zhang; Kritika M. Garg; Gang Song; Jonathan Martinez; Le Manh Hung; Vuong Tan Tu; Jérôme Fuchs; Lu Dong; Urban Olsson; Yuan Huang; et al. (Zoologica Scripta, 2023)
Morphology has been a leading taxonomic guiding light to systematists for the last couple of hundred years. However, the genetic and – more recently – genomic revolution have produced numerous demonstrations of erroneous classifications that were based on labile morphological traits. We used thousands of genome‐wide markers to shed light on evolutionary dynamics in a confusing and taxonomically obscure group of Asian Cyornis flycatchers. Using genomic data, we corroborated recent findings based on three mitochrondrial and five nuclear genes that the two taxa hainanus and klossi which were previously treated as separate species ( Cyornis hainanus and Cyornis rubeculoides klossi , respectively) are genomically homogeneous and form a single species, C. hainanus . We also uncovered a novel case of interbreeding between C. hainanus and a non‐sister species, C. glaucicomans , illustrating these flycatchers' ability to hybridise in marginal situations even after substantial times of divergence. Our study illustrates how genome‐wide loci can shed light on complicated taxonomic problems, resulting in a better integration of phenotypic and genotypic data.

Flexible and multifaceted: the plasticity of renin-expressing cells - Katharina A. E. Broeker; Julia Schrankl; Michaela A. A. Fuchs; Armin Kurtz (Pflügers Archiv - European Journal of Physiology, 2022)
The protease renin, the key enzyme of the renin–angiotensin–aldosterone system, is mainly produced and secreted by juxtaglomerular cells in the kidney, which are located in the walls of the afferent arterioles at their entrance into the glomeruli. When the body’s demand for renin rises, the renin production capacity of the kidneys commonly increases by induction of renin expression in vascular smooth muscle cells and in extraglomerular mesangial cells. These cells undergo a reversible metaplastic cellular transformation in order to produce renin. Juxtaglomerular cells of the renin lineage have also been described to migrate into the glomerulus and differentiate into podocytes, epithelial cells or mesangial cells to restore damaged cells in states of glomerular disease. More recently, it could be shown that renin cells can also undergo an endocrine and metaplastic switch to erythropoietin-producing cells. This review aims to describe the high degree of plasticity of renin-producing cells of the kidneys and to analyze the underlying mechanisms.

Hybrid conferences: opportunities, challenges and ways forward - Eleonora Puccinelli; Daniela Zeppilli; Paris V. Stefanoudis; Annaïg Wittische-Helou; Marjorie Kermorgant; Sandra Fuchs; Lénaïck Menot; Erin E. Easton; Alexandra A-T. Weber (Frontiers in Marine Science, 2022)
Hybrid conferences are in-person events that have an online component. This type of meeting format was rare before the COVID-19 pandemic, but started to become more common recently given the asynchronous global progression of the pandemic, the uneven access to vaccines and different travel regulations among countries that led to a large proportion of participants being unable to attend conferences in person. Here we report the organization of a middle-sized (581 participants: 159 onsite, 422 online) international hybrid conference that took place in France in September 2021. We highlight particular organizational challenges inherent to this relatively new type of meeting format. Furthermore, we surveyed both in-person and online participants to better understand their conference experience and to propose improvements based on the feedback received. Finally, we compare the advantages and disadvantages of three types of conferences (onsite-only, online-only and hybrid) and suggest that hybrid events should be favored in the future because they offer the most flexibility to participants. We conclude by proposing suggestions and ways forward to maximize accessibility and inclusivity of hybrid conferences. Our study brings novel insights on the challenges and opportunities created by hybrid conferences, by reporting not only the organizing committee experience but also by considering the participants’ perspective.

HIV-related drivers of sexual compulsivity and sexuality in sexual minority men who use methamphetamine - Hema R. Kondur; Tae K. Lee; Roger McIntosh; Hetta Gouse; Robert Paul; Christian Grov; Dietmar Fuchs; Walter Gómez; Samantha E. Dilworth; Torsten B. Neilands; Adam W. Carrico (Journal of NeuroVirology, 2022)

Knowledge, Attitudes, Willingness to Pay, and Patient Preferences About Genetic Testing and Subsequent Risk Management for Cancer Prevention - Fangjian Guo; Jacqueline M. Hirth; Erika L. Fuchs; Leslie E. Cofie; Veronica Brown; Yong-Fang Kuo; Maria E. Fernandez; Abbey B. Berenson (Journal of Cancer Education, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Endothelin receptors in renal interstitial cells do not contribute to the development of fibrosis during experimental kidney disease - Thomas H. Neder; Julia Schrankl; Michaela A. A. Fuchs; Katharina A. E. Broeker; Charlotte Wagner (Pflügers Archiv - European Journal of Physiology, 2021)
Renal interstitial fibrosis is characterized by the development of myofibroblasts, originating from resident renal and immigrating cells. Myofibroblast formation and extracellular matrix production during kidney damage are triggered by various factors. Among these, endothelins have been discussed as potential modulators of renal fibrosis. Utilizing mouse models of adenine nephropathy (AN) and unilateral ureter occlusion (UUO), this study aimed to investigate the contribution of endothelin signaling in stromal mesenchymal resident renal interstitial cells. We found in controls that adenine feeding and UUO caused marked upregulations of endothelin-1 (ET-1) gene expression in endothelial and in tubular cells and a strong upregulation of ET A -receptor (ET A -R) gene expression in interstitial and mesangial cells, while the gene expression of ET B -receptor (ET B -R) did not change. Conditional deletion of ET A -R and ET B -R gene expression in the FoxD1 stromal cell compartment which includes interstitial cells significantly reduced renal ET A -R gene expression and moderately lowered renal ET B -R gene expression. ET receptor (ET-R) deletion exerted no apparent effects on kidney development nor on kidney function. Adenine feeding and UUO led to similar increases in profibrotic and proinflammatory gene expression in control as well as in ET A flfl ET B flfl FoxD1 Cre+ mice (ET-Ko). In summary, our findings suggest that adenine feeding and UUO activate endothelin signaling in interstitial cells which is due to upregulated ET A -R expression and enhanced renal ET-1 production Our data also suggest that the activation of endothelin signaling in interstitial cells has less impact for the development of experimentally induced fibrosis.

Metagenomic analysis of nepoviruses: diversity, evolution and identification of a genome region in members of subgroup A that appears to be important for host range - J. M. Hily; N. Poulicard; J. Kubina; J. S. Reynard; A. S. Spilmont; M. Fuchs; O. Lemaire; E. Vigne (Archives of Virology, 2021)
Data mining and metagenomic analysis of 277 open reading frame sequences of bipartite RNA viruses of the genus Nepovirus , family Secoviridae , were performed, documenting how challenging it can be to unequivocally assign a virus to a particular species, especially those in subgroups A and C, based on some of the currently adopted taxonomic demarcation criteria. This work suggests a possible need for their amendment to accommodate pangenome information. In addition, we revealed a host-dependent structure of arabis mosaic virus (ArMV) populations at a cladistic level and confirmed a phylogeographic structure of grapevine fanleaf virus (GFLV) populations. We also identified new putative recombination events in members of subgroups A, B and C. The evolutionary specificity of some capsid regions of ArMV and GFLV that were described previously and biologically validated as determinants of nematode transmission was circumscribed in silico . Furthermore, a C-terminal segment of the RNA-dependent RNA polymerase of members of subgroup A was predicted to be a putative host range determinant based on statistically supported higher π (substitutions per site) values for GFLV and ArMV isolates infecting Vitis spp. compared with non- Vitis -infecting ArMV isolates. This study illustrates how sequence information obtained via high-throughput sequencing can increase our understanding of mechanisms that modulate virus diversity and evolution and create new opportunities for advancing studies on the biology of economically important plant viruses.

Complex interactions with nutrients and sediment alter the effects of predation on a reef‐building coral - Mallory M. Rice; Daniel G. Baldwin; Janine N. Fischer; Corinne Fuchs; Deron E. Burkepile (Marine Ecology, 2021)
Framework‐building corals create the three‐dimensional structure of coral reefs and are subject to predation from fishes, echinoderms, and gastropods. Anthropogenic stressors can magnify the effects of such top‐down pressure on foundation species. The gastropod Coralliophila violacea (Kiener, 1836) depletes coral energy reserves via predation, potentially increasing coral susceptibility to land‐based pollution (i.e., sediment accumulation and nutrient pollution). We hypothesized that sedimentation would worsen coral mortality, while nutrient enrichment would mitigate the harmful effects of sediment and predation on coral mortality by increasing the densities of algal symbionts. To test these hypotheses, we conducted in situ surveys of the fringing reefs in Mo'orea, French Polynesia to explore the relationships among massive Porites spp . cover, C. violacea densities, and sediment accumulation on coral colonies across low and high nutrient sites. We also conducted a factorial field experiment to test the interactions among these stressors on coral tissue mortality, symbiont densities, and chlorophyll. Massive Porites colonies at higher nutrient sites had C. violacea densities 13 times higher than at low nutrient sites but there was no difference in the amount of live tissue on coral colonies with or without snails among these sites. In our experiment, there were interactions between predation and nutrients as well as nutrients and sediment that impacted coral mortality. Sedimentation and predation by C. violacea increased coral tissue mortality independently by ~20%. Nutrient enrichment reduced this effect in corals under sedimentation or predation pressure by lowering coral tissue mortality by 18% and increasing algal symbiont densities by ~28%. Our results indicate that sediment does not magnify top‐down pressure on this coral, and that moderate nutrient enrichment may interact with predation in complex, unexpected ways to alter the responses of corals to top‐down pressure.

A high leukocyte count and administration of hydrocortisone hamper PCR-based diagnostics for bloodstream infections - Silke Huber; Johannes Weinberger; Matthias Pilecky; Ingo Lorenz; Anita Schildberger; Viktoria Weber; Stefan Fuchs; Wilfried Posch; Ludwig Knabl; Reinhard Würzner; Andreas E. Posch; Dorothea Orth-Höller (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Tryptophan depletion predicts lower positive affect in sexual minority men living with HIV who use methamphetamine - Ji-Young Lee; Tiffany R. Glynn; Judith T. Moskowitz; Dietmar Fuchs; Torsten B. Neilands; Samantha E. Dilworth; Daniel J. Feaster; Allan Rodriguez; Adam W. Carrico (Journal of NeuroVirology, 2021)

Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites - Jacob A. Nelson; Oscar Pérez‐Priego; Sha Zhou; Rafael Poyatos; Yao Zhang; Peter D. Blanken; Teresa E. Gimeno; Georg Wohlfahrt; Ankur R. Desai; Beniamino Gioli; Jean‐Marc Limousin; Damien Bonal; et al. (Global Change Biology, 2020)
We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants’ water use for global water and carbon cycling in a changing climate.

Tryptophan degradation is associated with risk-taking propensity in methamphetamine users with treated HIV infection - Jared Lee; Ji-Young Lee; Christina S. Meade; Michael Cohn; Antonio Chahine; Samantha E. Dilworth; Jessica F. Magidson; Hetta Gouse; Dietmar Fuchs; Adam W. Carrico (Journal of NeuroVirology, 2020)

Nutrient Pollution and Predation Differentially Affect Innate Immune Pathways in the Coral Porites porites - Katherine E. Dougan; Mark C. Ladd; Corinne Fuchs; Rebecca Vega Thurber; Deron E. Burkepile; Mauricio Rodriguez-Lanetty (Frontiers in Marine Science, 2020)

MDH1 deficiency is a metabolic disorder of the malate–aspartate shuttle associated with early onset severe encephalopathy - Melissa H. Broeks; Hanan E. Shamseldin; Amal Alhashem; Mais Hashem; Firdous Abdulwahab; Tarfa Alshedi; Iman Alobaid; Fried Zwartkruis; Denise Westland; Sabine Fuchs; Nanda M. Verhoeven-Duif; Judith J. M. Jans; et al. (Human Genetics, 2019)

Isolation and characterization of microsatellites loci in Spondias purpurea (Anacardiaceae) and cross amplification in congeneric species - E. Jacob Cristóbal-Pérez; Eric J. Fuchs; Nick Harvey; Mauricio Quesada (Molecular Biology Reports, 2019)

Establishing species-specific sexing markers suitable for non-invasive samples of species lacking genomic resources: an example using the highly endangered common hamster Cricetus cricetus - Tobias E. Reiners; Melanie Fuchs; Frank Hailer; Axel Janke; Carsten Nowak (Conservation Genetics Resources, 2017)

A bibliometric-based evaluation on environmental research in the Arab world - SH. H. Zyoud; D. Fuchs-Hanusch; S. H. Zyoud; A. E. Al-Rawajfeh; H. Q. Shaheen (International Journal of Environmental Science and Technology, 2017)

Genomic and physiological analyses of ‘ Reinekea forsetii ’ reveal a versatile opportunistic lifestyle during spring algae blooms - Burak Avcı; Richard L. Hahnke; Meghan Chafee; Tanja Fischer; Harald Gruber‐Vodicka; Halina E. Tegetmeyer; Jens Harder; Bernhard M. Fuchs; Rudolf I. Amann; Hanno Teeling (Environmental Microbiology, 2017)
Summary Gammaproteobacterial Reinekea spp. were detected during North Sea spring algae blooms in the years 2009‐2012, with relative abundances of up to 16% in the bacterioplankton. Here, we explore the ecophysiology of ‘R. forsetii' strain Hel1_31_D35 that was isolated during the 2010 spring bloom using (i) its manually annotated, high‐quality closed genome, (ii) re‐analysis of in situ data from the 2009–2012 blooms and (iii) physiological tests. High resolution analysis of 16S rRNA gene sequences suggested that ‘R. forsetii' dominated Reinekea populations during these blooms. This was corroborated by retrieval of almost complete Hel1_31_D35 genomes from 2009 and 2010 bacterioplankton metagenomes. Strain Hel1_31_D35 can use numerous low‐molecular weight substrates including diverse sugar monomers, and few but relevant algal polysaccharides such as mannan, α‐glucans, and likely bacterial peptidoglycan. It oxidizes thiosulfate to sulfate, and ferments under anoxic conditions. The strain can attach to algae and thrives at low phosphate concentrations as they occur during blooms. Its genome encodes RTX toxin and secretion proteins, and in cultivation experiments Hel1_31_D35 crude cell extracts inhibited growth of a North Sea Polaribacter strain. Our data suggest that the combination of these traits make strain Hel1_31_D35 a versatile opportunist that is particularly competitive during spring phytoplankton blooms.

Localization of the human neonatal Fc receptor (FcRn) in human nasal epithelium - Sara Heidl; Isabella Ellinger; Verena Niederberger; Eva E. Waltl; Renate Fuchs (Protoplasma, 2016)

Assessing the influence of historic net and gross land changes on the carbon fluxes of Europe - Richard Fuchs; Catharina J. E. Schulp; Geerten M. Hengeveld; Peter H. Verburg; Jan G. P. W. Clevers; Mart‐Jan Schelhaas; Martin Herold (Global Change Biology, 2016)
Legacy effects of land cover/use on carbon fluxes require considering both present and past land cover/use change dynamics. To assess past land use dynamics, model‐based reconstructions of historic land cover/use are needed. Most historic reconstructions consider only the net area difference between two time steps (net changes) instead of accounting for all area gains and losses (gross changes). Studies about the impact of gross and net land change accounting methods on the carbon balance are still lacking. In this study, we assessed historic changes in carbon in soils for five land cover/use types and of carbon in above‐ground biomass of forests. The assessment focused on Europe for the period 1950 to 2010 with decadal time steps at 1‐km spatial resolution using a bookkeeping approach. To assess the implications of gross land change data, we also used net land changes for comparison. Main contributors to carbon sequestration between 1950 and 2010 were afforestation and cropland abandonment leading to 14.6 PgC sequestered carbon (of which 7.6 PgC was in forest biomass). Sequestration was highest for old‐growth forest areas. A sequestration dip was reached during the 1970s due to changes in forest management practices. Main contributors to carbon emissions were deforestation (1.7 PgC) and stable cropland areas on peaty soils (0.8 PgC). In total, net fluxes summed up to 203 TgC yr −1 (98 TgC yr −1 in forest biomass and 105 TgC yr −1 in soils). For areas that were subject to land changes in both reconstructions (35% of total area), the differences in carbon fluxes were about 68%. Overall for Europe the difference between accounting for either gross or net land changes led to 7% difference (up to 11% per decade) in carbon fluxes with systematically higher fluxes for gross land change data.

A prospective study of oral contraceptive use and colorectal adenomas - Brittany M. Charlton; Edward Giovannucci; Charles S. Fuchs; Andrew T. Chan; Jung Eun Lee; Yin Cao; Stacey A. Missmer; Bernard A. Rosner; Susan E. Hankinson; Walter Willett; Kana Wu; Karin B. Michels (Cancer Causes & Control, 2016)

Benchmarking the scientific output of industrial wastewater research in Arab world by utilizing bibliometric techniques - Shaher H. Zyoud; Aiman E. Al-Rawajfeh; Hafez Q. Shaheen; Daniela Fuchs-Hanusch (Environmental Science and Pollution Research, 2016)

Sensory feedback in cockroach locomotion: current knowledge and open questions - A. Ayali; E. Couzin-Fuchs; I. David; O. Gal; P. Holmes; D. Knebel (Journal of Comparative Physiology A, 2015)

CXCR4 antibody treatment suppresses metastatic spread to the lung of intratibial human osteosarcoma xenografts in mice - Patrick Brennecke; Matthias J. E. Arlt; Carmen Campanile; Knut Husmann; Ana Gvozdenovic; Tiziana Apuzzo; Marcus Thelen; Walter Born; Bruno Fuchs (Clinical & Experimental Metastasis, 2014)

Chronic nutrient enrichment increases prevalence and severity of coral disease and bleaching - Rebecca L. Vega Thurber; Deron E. Burkepile; Corinne Fuchs; Andrew A. Shantz; Ryan McMinds; Jesse R. Zaneveld (Global Change Biology, 2014)
Nutrient loading is one of the strongest drivers of marine habitat degradation. Yet, the link between nutrients and disease epizootics in marine organisms is often tenuous and supported only by correlative data. Here, we present experimental evidence that chronic nutrient exposure leads to increases in both disease prevalence and severity and coral bleaching in scleractinian corals, the major habitat‐forming organisms in tropical reefs. Over 3 years, from June 2009 to June 2012, we continuously exposed areas of a coral reef to elevated levels of nitrogen and phosphorus. At the termination of the enrichment, we surveyed over 1200 scleractinian corals for signs of disease or bleaching. Siderastrea siderea corals within enrichment plots had a twofold increase in both the prevalence and severity of disease compared with corals in unenriched control plots. In addition, elevated nutrient loading increased coral bleaching; Agaricia spp. of corals exposed to nutrients suffered a 3.5‐fold increase in bleaching frequency relative to control corals, providing empirical support for a hypothesized link between nutrient loading and bleaching‐induced coral declines. However, 1 year later, after nutrient enrichment had been terminated for 10 months, there were no differences in coral disease or coral bleaching prevalence between the previously enriched and control treatments. Given that our experimental enrichments were well within the ranges of ambient nutrient concentrations found on many degraded reefs worldwide, these data provide strong empirical support to the idea that coastal nutrient loading is one of the major factors contributing to the increasing levels of both coral disease and coral bleaching. Yet, these data also suggest that simple improvements to water quality may be an effective way to mitigate some coral disease epizootics and the corresponding loss of coral cover in the future.

Approach to Cerebrospinal Fluid (CSF) Biomarker Discovery and Evaluation in HIV Infection - Richard W. Price; Julia Peterson; Dietmar Fuchs; Thomas E. Angel; Henrik Zetterberg; Lars Hagberg; Serena Spudich; Richard D. Smith; Jon M. Jacobs; Joseph N. Brown; Magnus Gisslen (Journal of Neuroimmune Pharmacology, 2013)

Rediscovering ACE: novel insights into the many roles of the angiotensin-converting enzyme - Romer A. Gonzalez-Villalobos; Xiao Z. Shen; Ellen A. Bernstein; Tea Janjulia; Brian Taylor; Jorge F. Giani; Wendell-Lamar B. Blackwell; Kandarp H. Shah; Peng D. Shi; Sebastien Fuchs; Kenneth E. Bernstein (Journal of Molecular Medicine, 2013)

An additional substrate binding site in a bacterial phenylalanine hydroxylase - Judith A. Ronau; Lake N. Paul; Julian E. Fuchs; Isaac R. Corn; Kyle T. Wagner; Klaus R. Liedl; Mahdi M. Abu-Omar; Chittaranjan Das (European Biophysics Journal, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Evidence for distinct populations of human Merkel cells - A.-C. Eispert; F. Fuchs; J. M. Brandner; P. Houdek; E. Wladykowski; Ingrid Moll (Histochemistry and Cell Biology, 2009)

Multiple interspecies recombination events within RNA2 of Grapevine fanleaf virus and Arabis mosaic virus - E. Vigne; A. Marmonier; M. Fuchs (Archives of Virology, 2008)

New insights into the role of angiotensin-converting enzyme obtained from the analysis of genetically modified mice - Xiao Z. Shen; Hong D. Xiao; Ping Li; Chentao X. Lin; Sandrine Billet; Derick Okwan-Duodu; Jon W. Adams; Ellen A. Bernstein; Yi Xu; Sebastien Fuchs; Kenneth E. Bernstein (Journal of Molecular Medicine, 2008)

Improvement and application of the biocontrol fungus Stagonospora convolvuli LA39 formulation for efficient control of Calystegia sepium and Convolvulus arvensis - D. Boss; E. Schläpfer; J. Fuchs; G. Défago; M. Maurhofer (Journal of Plant Diseases and Protection, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Microbial control of phosphate in the nutrient‐depleted North Atlantic subtropical gyre - Mikhail V. Zubkov; Isabelle Mary; E. Malcolm S. Woodward; Phillip E. Warwick; Bernhard M. Fuchs; David J. Scanlan; Peter H. Burkill (Environmental Microbiology, 2007)
Summary Little is known about the dynamics of dissolved phosphate in oligotrophic areas of the world's oceans, where concentrations are typically in the nanomolar range. Here, we have budgeted phosphate uptake by the dominant microbial groups in order to assess the effect of the microbial control of this depleted nutrient in the North Atlantic gyre. Low concentrations (2.2 ± 1.2 nM) and rapid microbial uptake (2.1 ± 2.4 nM day −1 ) of bioavailable phosphate were repeatedly determined in surface waters of the North Atlantic oligotrophic gyre during spring and autumn research cruises, using a radiotracer dilution bioassay technique. Upper estimates of the concentration of bioavailable phosphate were 7–55% of the dissolved mineral phosphate suggesting that a considerable part of the chemically measured nanomolar phosphate was in a form unavailable for direct microbial uptake. A 1:1 relationship ( r 2 = 0.96, P Prochlorococcus phototrophic cyanobacteria, were the two major competing groups for bioavailable phosphate. These heterotrophic bacteria had low nucleic acid content and 60% of them comprised of SAR11 clade cells based on the results of fluorescence in situ hybridization. Each of the two competing bacterial groups was responsible for an average of 45% of the phosphate uptake, while Synechococcus cyanobacteria (7%) and picoplanktonic algae (0.3%) played minor roles in direct phosphate uptake. We have demonstrated that phosphate uptake in the oligotrophic gyre is rapid and dominated by two bacterial groups rather than by algae.

Comparative spatial spread overtime of Zucchini Yellow Mosaic Virus (ZYMV) and Watermelon Mosaic Virus (WMV) in fields of transgenic squash expressing the coat protein genes of ZYMV and WMV, and in fields of nontransgenic squash - Ferdinand E. Klas; Marc Fuchs; Dennis Gonsalves (Transgenic Research, 2006)

Contributions of prolonged contingent and noncontingent cocaine exposure to enhanced reinstatement of cocaine seeking in rats - Tod E. Kippin; Rita A. Fuchs; Ronald E. See (Psychopharmacology, 2006)

Process metallurgy for high performance materials at RWTH Aachen/Germany - B. Friedrich; R. Fuchs; C. Kräutlein; C. Lochbichler; A. Lützerath; E. Milke; J. C. Stoephasius (BHM Berg- und Hüttenmännische Monatshefte, 2006)

A Prospective Study of Body Mass Index, Hypertension, and Smoking and the Risk of Renal Cell Carcinoma (United States) - Keith T. Flaherty; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Frank E. Speizer; Walter C. Willett; Gary C. Curhan (Cancer Causes & Control, 2005)

Characterization of a naturally occurring recombinant isolate of Grapevine fanleaf virus - E. Vigne; G. Demangeat; V. Komar; M. Fuchs (Archives of Virology, 2005)

Potentiation of cocaine-primed reinstatement of drug seeking in female rats during estrus - Tod E. Kippin; Rita A. Fuchs; Ritu H. Mehta; Jordan M. Case; Macon P. Parker; Heather A. Bimonte-Nelson; Ronald E. See (Psychopharmacology, 2005)

Influence of sex and estrous cyclicity on conditioned cue-induced reinstatement of cocaine-seeking behavior in rats - Rita A. Fuchs; K. Allison Evans; Ritu H. Mehta; Jordan M. Case; Ronald E. See (Psychopharmacology, 2005)

Differential involvement of the core and shell subregions of the nucleus accumbens in conditioned cue-induced reinstatement of cocaine seeking in rats - Rita A. Fuchs; K. Allison Evans; Macon C. Parker; Ronald E. See (Psychopharmacology, 2004)

A Myo7a mutation cosegregates with stereocilia defects and low-frequency hearing impairment - Charlotte R. Rhodes; Ronna Hertzano; Helmut Fuchs; Rachel E. Bell; Martin Hrabé de Angelis; Karen P. Steel; Karen B. Avraham (Mammalian Genome, 2004)

Neuromodulation for behavior in the locust frontal ganglion - Y. Zilberstein; E. Fuchs; L. Hershtik; A. Ayali (Journal of Comparative Physiology A, 2004)

Human papillomavirus-positive tonsillar carcinomas: a different tumor entity? - Jens P. Klussmann; Soenke J. Weissenborn; Ulrike Wieland; Volker Dries; Hans E. Eckel; Herbert J. Pfister; Pawel G. Fuchs (Medical Microbiology and Immunology, 2003)

Aspirin, other NSAIDs, and ovarian cancer risk (United States) - Kathleen M. Fairfield; David J. Hunter; Charles S. Fuchs; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2002)

Basolateral amygdala inactivation abolishes conditioned stimulus- and heroin-induced reinstatement of extinguished heroin-seeking behavior in rats - Rita A. Fuchs; Ronald E. See (Psychopharmacology, 2002)

Ecotoxicological Characterization of a Disposal Lagoon from a Munition Plant - J. S. Fuchs; M. L. Oneto; N. B. Casabé; O. Gómez Segura; R. Tarulla; M. Vaccarezza; C. Sánchez-Rivas; E. M. Kesten; E. J. Wood (Bulletin of Environmental Contamination and Toxicology, 2001)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Mutations of the gene encoding the transmembrane transporter protein ABC-C6 cause pseudoxanthoma elasticum - Berthold Struk; Li Cai; Stéphanie Zäch; Wan Ji; Joon Chung; Amanda Lumsden; Markus Stumm; Marcel Huber; Lori Schaen; Chung-Ah Kim; Lowell A. Goldsmith; Denis Viljoen; et al. (Journal of Molecular Medicine, 2000)

A 500-kb region on chromosome 16p13.1 contains the pseudoxanthoma elasticum locus: high-resolution mapping and genomic structure - Li Cai; Berthold Struk; Mark D. Adams; Wan Ji; Thomas Haaf; Hyung-Lyun Kang; So Hee Dho; Xuequn Xu; Franziska Ringpfeil; Julie Nancarrow; Stéphanie Zäch; Lori Schaen; et al. (Journal of Molecular Medicine, 2000)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Flight machinery dimensions of honeybees, Apis mellifera - H. R. Hepburn; S. E. Radloff; S. Fuchs (Journal of Comparative Physiology B, 1999)

Xanthine oxidase inhibition by allopurinol affects the reliability of urinary caffeine metabolic ratios as markers for N -acetyltransferase 2 and CYP1A2 activities - P. Fuchs; W. E. Haefeli; H. R. Ledermann; M. Wenk (European Journal of Clinical Pharmacology, 1999)

Esterases of Corbicula fluminea as Biomarkers of Exposure to Organophosphorus Pesticides - S. B. Basack; M. L. Oneto; J. S. Fuchs; E. J. Wood; E. M. Kesten (Bulletin of Environmental Contamination and Toxicology, 1998)

Uptake of poliovirus into the endosomal system of HeLa cells - P. Kronenberger; D. Schober; E. Prchla; O. Ofori-Anyinam; R. Vrijsen; B. Rombaut; D. Blaas; R. Fuchs; A. Boeyé (Archives of Virology, 1998)

Genetic basis of resistance to sugarcane mosaic virus in European maize germplasm - A. E. Melchinger; L. Kuntze; R. K. Gumber; T. Lübberstedt; E. Fuchs (Theoretical and Applied Genetics, 1998)

Predictive validity of the extinction/reinstatement model of drug craving - Rita A. Fuchs; L. T. L. Tran-Nguyen; Sheila E. Specio; Robert S. Groff; J. L. Neisewander (Psychopharmacology, 1998)

Transgenic Melon and Squash Expressing Coat Protein Genes of Aphid-borne Viruses do not Assist the Spread of an Aphid Non- transmissible Strain of Cucumber Mosaic Virus in the Field - Marc Fuchs; Ferdinand E. Klas; James R. McFerson; Dennis Gonsalves (Transgenic Research, 1998)

Anaerobic metabolism of l -phenylalanine via benzoyl-CoA in the denitrifying bacterium Thauera aromatica - Sabine Schneider; M. E.-S. Mohamed; G. Fuchs (Archives of Microbiology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Sequence comparison of the 3′-terminal parts of the RNA of four German isolates of sugarcane mosaic potyvirus (SCMV) - U. Oertel; J. Schubert; E. Fuchs (Archives of Virology, 1997)

Monoamine receptors in the prefrontal cortex of Tupaia belangeri during chronic psychosocial stress - G. Flügge; O. Ahrens; E. Fuchs (Cell and Tissue Research, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Enzymes of gluconeogenesis in the autotroph Methanobacterium thermoautotrophicum - G. Fuchs; H. Winter; I. Steiner; E. Stupperich (Archives of Microbiology, 1983)

A new approach to minimizing the number of animals used in acute toxicity testing and optimizing the information of test results - E. Schütz; H. Fuchs (Archives of Toxicology, 1982)

Die Ultrastruktur des Penetrationsvorganges von Olpidium brassicae an Kohlrabi-Wurzeln - D. E. Lesemann; W. H. Fuchs (Archives of Microbiology, 1970)

Elektronenmikroskopische Untersuchung ber die Vorbereitung der Infektion in encystierten Zoosporen von Olpidium brassicae - D. E. Lesemann; W. H. Fuchs (Archives of Microbiology, 1970)